Sharks in Macaronesia and Cabo Verde: species richness, conservation status and anthropogenic pressures - Jaquelino Varela; Jaquelino Varela; Catarina Pereira Santos; Catarina Pereira Santos; Catarina Pereira Santos; Emanuel Nunes; Emanuel Nunes; Vasco Pissarra; Vasco Pissarra; Stiven Pires; Bárbara P. Ribeiro; Bárbara P. Ribeiro; et al. (Frontiers in Marine Science)
The northeast Atlantic Ocean contains multiple habitats considered critical for shark conservation, including nursery areas, migratory corridors and aggregation sites. In this context, updating knowledge on shark diversity and the threats affecting them in this region is essential to defining priorities and implementing the right management and conservation measures. Here, we show that Macaronesian and Cabo Verde marine ecoregions are home to 78 shark species (comprising 26 families), and 56% are threatened with extinction. The Canary Islands revealed the greatest richness (with 56 species), followed by Cabo Verde (53), Madeira (52), and the Azores (45). Cabo Verde presents fewer similarities with the rest of the islands. We also found that: i) Azores share more species with the Canary Islands than Madeira (despite the greater geographical proximity with the latter), and ii) there are no oviparous species in the Cabo Verde archipelago, contrary to the Canary Islands (5), the Azores (4), and Madeira (3). Fishing and habitat degradation are the most relevant anthropogenic pressures for the region, with Cabo Verde having the highest number of endangered species (66%) and a greater magnitude and diversity of threats. As such, this archipelago presents the highest priority area for shark conservation due to the intense industrial fishing in its waters, poor management measures in combination with its greater vulnerability to climate change.